Study of the entrepreneurial profile of the administrators of the micro and small businesses in the southeast region of México (Nexo Revista Científica, 2021)
The city of San Andrés Tuxtla, in the state of Veracruz, is characterized by the fact that the commercial and service activity is made up of micro and small companies led by a single individual with two or three employees. This work shows the results of a study of the entrepreneurial profile of the administrators of micro and small companies in the region of San Andrés Tuxtla, Veracruz, with the purpose of establishing what skills and characteristics have kept them in a competitive economy in said municipality. The methodology applied for the development of the work was descriptive-exploratory and descriptive-quantitative when making a diagnosis that allowed us to know the business line of the companies under study, as well as the application of a survey to 212 business administrators. Among the results obtained, it is worth highlighting that of the 212 companies studied, 155 belong to the commercial branch and 57 to the services sector; the average age of entrepreneurs ranges between 31 and 40 years; In the same way, it can be concluded that the entrepreneurial profile of micro and small companies in the San Andrés Tuxtla region are young people who are proud of the activity they carry out, creative, with interest, capable, persistent, motivated and risk-taking. The study proposes suggestions for leaders to adopt aspects that can strengthen entrepreneurial skills to obtain greater results in their organizational work in the business.